2020
DOI: 10.1161/str.51.suppl_1.154
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 154: Diabetic Retinopathy and Risk of Stroke: A Secondary Analysis of Accord

Abstract: Background: Diabetic retinopathy is a common microvascular complication of diabetes. Previous research has shown that the macrovascular complications of diabetes, including stroke, are often comorbid with shared and, possibly, synergistic pathology. Methods: This is a secondary analysis of the subgroup of patients who enrolled in the ACCORD Eye study of ACCORD. The primary outcome is stroke during follow-up. The primary predictor was presence of diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Subgroup analysis for the type of diabetes yielded a pooled HR of 1.29 and 95% CI: 1.10; 1.50 in T2DM ( 21 ). In a secondary analysis of patients enrolled in the Action to Control Cardiovascular Risk in Diabetes (ACCORD) Eye Study in an adjusted Cox regression model, DR was independently associated with incident stroke (HR:1.52, 95% CI:1.05; 2.20) ( 22 ). Another prospective cohort study with 1,617 middle-aged people with diabetes observed that during a follow-up of 7.8 years, DR was associated with an increased risk of ischemic stroke (HR: 2.34, 95% CI: 1.13; 4.86) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subgroup analysis for the type of diabetes yielded a pooled HR of 1.29 and 95% CI: 1.10; 1.50 in T2DM ( 21 ). In a secondary analysis of patients enrolled in the Action to Control Cardiovascular Risk in Diabetes (ACCORD) Eye Study in an adjusted Cox regression model, DR was independently associated with incident stroke (HR:1.52, 95% CI:1.05; 2.20) ( 22 ). Another prospective cohort study with 1,617 middle-aged people with diabetes observed that during a follow-up of 7.8 years, DR was associated with an increased risk of ischemic stroke (HR: 2.34, 95% CI: 1.13; 4.86) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have extensive evidence that associates DR with other micro-and macrovascular complications of diabetes. Recently, it was reported that DR is associated with subclinical atherosclerosis (10)(11)(12)(13)(14), macrovascular comorbidities such as coronary disease (15)(16)(17)(18)(19)(20) and cerebrovascular accident (21)(22)(23)(24)(25)(26). Of interest, some studies have reported an association between cognitive impairment and the incidence of dementia [risk ratio (RR), 1.3; 95% confidence interval (CI), 1.27-1.58] (27,28), and the relation between DR and neurodegeneration diseases such as Parkinson's disease has been proposed but remains unclear (29).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a high frequency of circulatory signpost codes are predictive of congestive heart failure. A medium frequency of eye/adnexa signpost codes are predictive of diabetic retinopathy, stroke, and vascular dementia, all shown in the literature to be associated with ocular symptoms (Ho et al, 2009;Hwang et al, 2021;Wong et al, 2020). An application for how individual-level DETECT trajectories can be leveraged to ask temporal questions about order or quality of disease precursors at a population level is shown in Fig.…”
Section: Real-world Data Trajectory Analysismentioning
confidence: 99%
“…However, accruing evidence suggest that other factors such as diabetes-related microvascular complications might play a role [ 4 7 ]. Indeed, diabetic retinopathy was found to be associated with higher risk of stroke in people with type 2 diabetes [ 8 ]. The impact on stroke of microvascular disease in other vascular territories (such as the kidney) in individuals with type 2 diabetes has received less attention [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%